Intervención optométrica en paciente femenino de 14 años de edad con disminución de la agudeza visual y fotofobia atendido en la Óptica “San Alejo” Babahoyo, Los Ríos. - Coello Sellan, Elba Jerelyn (2025)
This clinical case study is based on the optometric intervention in a 14-year-old female patient with decreased visual acuity and photophobia, which the discomfort that occurs us blurred distance vision, considered a refractive error, or due to some pathology and ocular diseases. Therefore, photophobia or light sensitivity is a manifestation where people feel uncomfortable or uncomfortable being in bright places, which may be caused by various causes. On the other hand, the general objective of the case is to determine the cause that can cause these symptoms, therefore, as specific objectives, to analyze these symptoms, identify the ametropias and establish an adequate treatment for the improvement of visual quality. Several optometric examinations were performed in order to meet the objectives of this intervention and to achieve a suitable and recommended treatment to the patient to achieve a good improvement in her visual quality. In the results obtained, the definitive diagnosis of the patient presents a compound myopic astigmatism and mild photophobia, and she was given an appropriate treatment or air lenses with UV photochromic protection, and a follow-up plan to monitor the effects of treatment and make any changes if necessary. To conclude, he was recommended an exercise that would help him to improve his visual health, which applies a rule where for 20 minutes he has to look away from the screen, focus on an object that is 20 feet away and keep his gaze fixed on an object for 2o seconds.